THE VIOLENCE DURING POLICE INVESTIGATIONS REVIEWED FROM FIQH AL-JINAYAH - Awalia, Fadhila Tianti Mudi; Susilo, Dafa’ Alifta Akbar; Rachmawati, Andini; Abdurrahman, Usamah (International Conference on Humanity Education and Society (ICHES), 2024)
In the field of law enforcement, cases of violence perpetrated by the police often occur within the context of police investigations. Acts of violence during police inquiries are complex and controversial. Police violence in the investigative process, aimed at obtaining evidence or confessions, cannot be justified under any circumstances. In Islamic law, acts of violence by law enforcement officials during investigations are also prohibited, as regulated in the fiqh jinayah which outlines clear penalties for offenders. The objective of this research is to comprehend the occurrence of violence during police investigations and examine the jurisprudential perspective on such cases. This study falls under legal research, particularly normative juridical research, involving an examination of legal principles. It is a literature review where data is obtained from existing literature. The research employs descriptive analysis and an analytical approach to the phenomenon of violence in police investigations. After analysis, it can be concluded that acts of violence in police investigations violate Regulation of the Chief of the Indonesian National Police (Kapolri) Number 8 of 2009 and Regulation of the Chief of the Indonesian National Police Number 14 of 2011. From the perspective of fiqh in criminal jurisprudence, cases of violence during investigations can be categorized as jarimah Qishash and jarimah ta'zir, where perpetrators of violence should receive similar punishment. The application of ta'zir depends on the discretion of the judge imposing the penalty. Recommendations regarding these cases include the necessity for investigations to adhere more closely to established regulations, such as those set by the Chief of Police or fiqh jinayah, concerning the investigative process. Relevant authorities should also conduct stricter oversight of investigative procedures to prevent further violence during investigations.